2007
DOI: 10.1038/ismej.2007.99
|View full text |Cite
|
Sign up to set email alerts
|

A multiphasic characterization of the impact of the herbicide acetochlor on freshwater bacterial communities

Abstract: Acetochlor is the third most frequently detected herbicide in natural waters; however, it is unknown if exposure to environmentally relevant concentrations of acetochlor will impact bacterial community structure and function. This study examined the impact of acetochlor on freshwater heterotrophic bacteria number, and community structure and function using direct counting, community level physiological profiling (CLPP) and denaturing gradient gel electrophoresis (DGGE) analysis. Acetochlor concentration did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…In addition to photosynthetic microorganisms, which are directly impacted by herbicides because they share some physiological metabolisms with terrestrial plants, these compounds can also have direct impacts on bacteria. For example, in a study of Foley et al (2008), DGGE fingerprinting showed that freshwater bacterial communities exposed to acetochlor, an inhibitor of cell growth and division, displayed reduced diversity. However, contradictory results have been obtained, and, for example Tadonleke et al (2009) did not find any significant impact of diuron, a phenylurea herbicide, on bacteria, whereas previous studies had seemed to do so.…”
Section: Impact Of Herbicides On the Composition And Structure Of Frementioning
confidence: 99%
“…In addition to photosynthetic microorganisms, which are directly impacted by herbicides because they share some physiological metabolisms with terrestrial plants, these compounds can also have direct impacts on bacteria. For example, in a study of Foley et al (2008), DGGE fingerprinting showed that freshwater bacterial communities exposed to acetochlor, an inhibitor of cell growth and division, displayed reduced diversity. However, contradictory results have been obtained, and, for example Tadonleke et al (2009) did not find any significant impact of diuron, a phenylurea herbicide, on bacteria, whereas previous studies had seemed to do so.…”
Section: Impact Of Herbicides On the Composition And Structure Of Frementioning
confidence: 99%
“…Spawn et al (1997) stated that alachlor exposure for 21 days led to a reduction of the algal biomass as measured by chlorophyll a up to 10 μg L −1 and changes in algal community structure and density up to 30 μg L −1 . Foley et al (2008) underlined that acetochlor exposure (96 h), which has similar toxicological mechanisms to alachlor, did not result in significant impact on bacterial community structure analyzed by DGGE at environmental concentrations (1 and 5 μg L −1 ).…”
Section: Community-level Response To Herbicide Exposurementioning
confidence: 98%
“…The number of carbon sources utilized by the bacteria communities from untreated and treated biofilms was calculated as the sum of the number of wells exhibiting absorbance greater than 0.25 OD (Foley et al 2008) and was run using an analysis of similarity (ANOSIM) on Bray-Curtis similarity matrices generated from the absorbance data with PRIMERr v6 software (Clarke 1993).…”
Section: Experimental Design and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations